2009
DOI: 10.1016/j.ejcts.2009.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic treatment with levosimendan: a retrospective matched-control study of patients with reduced left ventricular function

Abstract: Prophylactic infusion of levosimendan initiated before weaning from CPB did not lead to superior haemodynamic parameters (CI, SVI, SvO(2)) compared to controls. Levosimendan reduced MAP and increased the need for norepinephrine postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 24 publications
2
8
2
Order By: Relevance
“…In line with earlier publications MAP, EDP and CPP were significantly reduced by infusion of LEV in HF animals (Lilleberg et al 1998, Tassani et al 2002, Kolseth et al 2009. The mechanistic description of a vasodilation response by LEV is ascribed to opening of ATP-dependent K + -channels in myocytes of blood vessels (Yokoshiki et al 1997a, Yokoshiki & Sperelakis 2003.…”
Section: Discussionsupporting
confidence: 56%
“…In line with earlier publications MAP, EDP and CPP were significantly reduced by infusion of LEV in HF animals (Lilleberg et al 1998, Tassani et al 2002, Kolseth et al 2009. The mechanistic description of a vasodilation response by LEV is ascribed to opening of ATP-dependent K + -channels in myocytes of blood vessels (Yokoshiki et al 1997a, Yokoshiki & Sperelakis 2003.…”
Section: Discussionsupporting
confidence: 56%
“…217,219 Although cohort size was small in these studies, all reported positive haemodynamic outcomes, albeit with insufficient power to evaluate mortality. Nevertheless, Landoni found decreased mortality following administration of levosimendan in patients taking catecholamines 220 and also in patients undergoing heart surgery.…”
Section: Levosimendan and Conditioningmentioning
confidence: 98%
“…[98] Preliminary data suggest that prophylactic administration of levosimedan in patients with severe LV dysfunction improves ventricular performance and enhances primary weaning from CPB with lesser need for additional inotropic or mechanical therapy. [99][100][101][102][103] Phosphodiesterase inhibitors (PDEI) such as milrinone and enoxinone inhibit breakdown of cyclic adenosine monophosphate (cAMP) resulting in increased inotropy and decreased vascular tone. [104] In the PRIMACORP trial, the prophylactic administration of high-dose milrinone was associated with a 64% relative risk reduction in the development of LCOS following congenital cardiac operations.…”
Section: Prophylactic Interventionsmentioning
confidence: 99%